1995
DOI: 10.1017/s1357729800013874
|View full text |Cite
|
Sign up to set email alerts
|

Production, carcass and meat quality traits of F2-crosses between European Wild Pigs and domestic pigs including halothane gene carriers

Abstract: A pedigree originally designed for pig genome mapping was used in order to study carcass and muscle development as well as meat quality ofF 2 -crosses between the European Wild Pig and the domestic Large White pig (no. = 191). As a marker for the influence of genes inherited from the 'wild' and domestic grandparents, grouping based on the length of the small intestine was used. The pigs were also typed for genetic polymorphism at the calcium release channel (CRO locus controlling halothane susceptibility in pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
3
17
2
Order By: Relevance
“…The results of the present study differ from those described by those authors in terms of hot carcass weight and loin depth, which were higher in Nn than in NN animals (p < 0.05). Hamilton et al (2000), Fisher et al (2000a), Lundstrom et al (1995) and McPhee and Trout (1995) found shorter carcasses in Nn animals compared to NN animals, in contrast to the present study in which no significant difference in MLC traits was observed between genotypes (p > 0.05). However, Miller et al (1999) also observed no difference in carcass length between NN and Nn genotypes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of the present study differ from those described by those authors in terms of hot carcass weight and loin depth, which were higher in Nn than in NN animals (p < 0.05). Hamilton et al (2000), Fisher et al (2000a), Lundstrom et al (1995) and McPhee and Trout (1995) found shorter carcasses in Nn animals compared to NN animals, in contrast to the present study in which no significant difference in MLC traits was observed between genotypes (p > 0.05). However, Miller et al (1999) also observed no difference in carcass length between NN and Nn genotypes.…”
Section: Discussioncontrasting
confidence: 99%
“…These authors suggested that this gene might have been removed from pig populations, since their results indicated only a small effect of the PSS gene on lean meat content. Lundstrom et al (1995), studying F 2 crosses between European wild pigs and Large White animals, found no significant difference in growth rate between PSS genotypes, as also observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The infinitesimal model is attractive as it facilitates simple and elegant statistical descriptions of inheritance, such as predictable changes in genetic variance as a result of selection [5]. The discovery of a small number of genes of very large effect, such as the effect of the Hal gene on meat quality in pigs [17], led to a mixed model of inheritance of quantitative traits with many genes of small effect and rare genes of very large effect.…”
Section: Introductionmentioning
confidence: 99%
“…All 12 groups were fed a commercial diet (12.3 MJ, 16.8% crude protein) ad libitum. Phenotypical measurements included daily weight gain, ultrasonic measurements of fat depth at 70 and 90 kg and several carcass traits (Lundström et al, 1995) as compiled in Table 1. …”
mentioning
confidence: 99%